1982
DOI: 10.1111/j.1540-4560.1982.tb01771.x
|View full text |Cite
|
Sign up to set email alerts
|

Group Membership and Place Meanings in an Urban Neighborhood

Abstract: The changing nature of cities has raised serious questions concerning the quality of neighborhood and community life. It is essential to reflect on the meaning of neighborhoods and their function for urban dwellers. The role of group membership in place meanings is considered, using an environmental perspective that acknowledges the importance of places to an individual's sense of identity. A small case study of a Hasidic sect with a distinctive life style provides an opportunity to assess the contribution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 9 publications
0
39
0
Order By: Relevance
“…Today, Little Saigon is replete with signs, symbols, language, food and artifacts that constitute the core of the Vietnamese-American culture (see also Rivlin, 1982Rivlin, , 1987. What began in the 1970s with a few shops has grown today to include over 2000 businesses including major shopping centers, mini malls, super markets, restaurants, professional of¢ces, nail salons, £ower shops, bakeries and other services.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Today, Little Saigon is replete with signs, symbols, language, food and artifacts that constitute the core of the Vietnamese-American culture (see also Rivlin, 1982Rivlin, , 1987. What began in the 1970s with a few shops has grown today to include over 2000 businesses including major shopping centers, mini malls, super markets, restaurants, professional of¢ces, nail salons, £ower shops, bakeries and other services.…”
Section: Methodsmentioning
confidence: 99%
“…Rivlin (1982Rivlin ( , 1987, describing the intense commitment of the Lubavitch Jewish community, argues that it is the totality of their religious immersion and experience a¡orded by their Crown Heights neighborhood (such as the presence of the Rabbi and the network of kosher shops, mikvahs, yeshivas, synagogues and other supportive institutions) that led to their attachment to place. Loss of such places, according to Fried (1963, p. 232), represents a 'disruption in one's relationship to the past, to the present and the future.…”
Section: Ethnic Enclaves Place Identity and Attachmentmentioning
confidence: 99%
“…Sense of community has been linked to place attachment at the individual and community scale. Rivlin's (1987) study of a Brooklyn neighborhood found that attachment to the neighborhood served as a precondition for the development of a sense of community among neighbors. Both sense of community and place attachment are linked to participation, consequently sense of community has become a key planning goal (Morris, 1996;Perkins, Brown and Taylor, 1996).…”
Section: Sense Of Communitymentioning
confidence: 99%
“…According to Relph (1976:1) ''to be human is to live in a world that is filled with significant places.'' Scholars from anthropology, geography, sociology, and environmental psychology have looked at a variety of ''significant places'' such as, enclaves (Gans, 1962;Rivlin, 1982Rivlin, , 1987Abrahamson, 1996;Mazumdar & Mazumdar, 2000), plazas (Low, 1992), homes (Marcus, 1992;Mazumdar & Mazumdar, 1993, 1999, and compounds (Pellow, 1992), among others. From these studies we learn that ''significant places'' provide ''stability and security'' (Brown & Perkins, 1992), act as ''anchors'' (Marcus, 1992), and ''symbolic life line [s]'' (Hummon, 1989), and become ''fields of care'' (Relph, 1976).…”
Section: Religion Place Attachment and Identitymentioning
confidence: 99%